Orchid discoveries in the Caribbean: A new Lepanthes (Pleurothallidinae) with a gigantic disc-shaped lip endemic to Cuba - Restrepo, Eugenio; Soto-Calvo, Manuel Alejandro; Morales-Martínez, Alelí (Phytotaxa, 2022)
A new species of Lepanthes from Eastern Cuba, restricted to a small locality in the province of Guantánamo, where it grows lithophytically adjacent to the Río Duaba, near sea level is described and illustrated. This new species can be easily distinguished from other Cuban species by its small plant size, no more than 2 cm long, bearing a relatively large flower with reflexed sepals, an entire disc-shaped lip, compounded by two reniform basal lobes without an appendix, being easily one of the largest lips within the Lepanthes genus from Cuba.